2009
DOI: 10.1016/j.drugpo.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Regulating khat—Dilemmas and opportunities for the international drug control system

Abstract: Khat is the latest psychoactive plant based substance to become available on a global market. In contrast to other traditional substances, the use of khat is expanding rapidly, as a result of the dispersion of people from the Horn of Africa and particularly from Somalia as consequence of ongoing civil war, and because production and consumption is increasing across Africa. The sudden arrival of khat in new settings poses challenges to the regulatory arrangements of societies where the drug was hitherto unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 10 publications
0
34
0
2
Order By: Relevance
“…Il persiste de nombreuses inconnues quant aux effets des autres composants du khat, mais la parenté chimique de la cathinone avec l'amphétamine et des mécanismes d'action similaires sont autant d'arguments pour justifier d'inscrire le khat sur la liste des stupéfiants réglementés [3,4,67].…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Il persiste de nombreuses inconnues quant aux effets des autres composants du khat, mais la parenté chimique de la cathinone avec l'amphétamine et des mécanismes d'action similaires sont autant d'arguments pour justifier d'inscrire le khat sur la liste des stupéfiants réglementés [3,4,67].…”
Section: Resultsunclassified
“…En Europe, deux groupes distincts d'usagers sont identifiés [3]. S'il existe un intérêt croissant chez des jeunes pour la consommation de plantes et de substances psychotropes non réglementées via les sites internet ou des boutiques spécialisées, la majorité des usagers en Europe concerne les migrants de Somalie, d'Éthiopie, du Yémen et du Kenya, et leurs descendants [4]. La qualité des enquêtes de consommation est cependant insuffisante pour connaître avec précision les prévalences d'usage [5].…”
Section: Introductionunclassified
“…As noted already questions on khat are not included as a standardised item in most adult or youth surveys conducted by EU Member States (EMCDDA, 2002). Nevertheless, khat use is sporadically reported in Europe as a substance of choice among immigrants from Somalia, Ethiopia, Kenya and Yemen (Klein et al, 2009). There are a few published studies of khat use by immigrant communities in European countries (ACMD, 2005).…”
Section: Khat Usementioning
confidence: 99%
“…The discussion is particularly acute in Kabarole District in the Western region, one of the main growing areas. Police, local government officials and civil society groups have united in their negative views about the effects of khat because, as they see it (Klein et al, 2009):…”
Section: Rape and Violencementioning
confidence: 99%
“…WHO reviews in the 1950s, 1970s and 1980s also found that there was insufficient medical evidence of harm. In 2005 the Advisory Council on the Misuse of Drugs undertook a major review of khat in the UK, and recommended that the substance remain legal, but doubts persist amongst policy makers, as there is a lack of good quality studies on the effects of khat use (Anderson and Carrier, 2006;Klein and Beckerleg, 2007;Klein et al, 2009). As khat continues along a pathway to international prohibition, arguments about several types of harm by khat use are deployed by policy makers: chewing causes: ill health (ACMD, 2005;Anderson et al, 2007); psychiatric disorders (Dhadphale and Omolo, 1988;Odenwald, 2007;Warfa et al, 2007), and socio-economic hardship for the families of mostly male consumers (Borelli and Perali, 2004;Kennedy, 1987).…”
Section: Introductionmentioning
confidence: 99%